1996
DOI: 10.1002/(sici)1096-9896(199605)179:1<10::aid-path540>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

EARLY EXPRESSION OF bcl‐2 PROTEIN IN THE ADENOMA–CARCINOMA SEQUENCE OF COLORECTAL NEOPLASIA

Abstract: bcl-2 was originally identified as an oncogene involved in follicular lymphomas as a result of chromosomal translocation (14;18). It is now believed that bcl-2 is implicated in the regulation of cell death by inhibiting apoptosis and that its expression is not restricted to haematopoietic cells, but is also present in many epithelial and mesenchymal tissues. Recent studies have analysed the expression of this molecule in a variety of non-lymphoid malignancies including lung, breast, prostate, and nasopharyngea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
17
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 0 publications
5
17
0
Order By: Relevance
“…Other reports have shown that p53 can down-regulate bcl-2 gene expression (Miyashita et al, 1994) and in a breast cell line bcl-2 was down-regulated by overexpression of a mutant p53 (Halder et al, 1994). In a previous study (Kaklamanis et al, 1996), carcinomas arising from adenomas showed loss of bcl-2 (85% positive adenomas compared with 25% positive carcinomas), implying that during the adenomacarcinoma progression, at the time when p53 mutations usually take place, bcl-2 expression is down-regulated.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Other reports have shown that p53 can down-regulate bcl-2 gene expression (Miyashita et al, 1994) and in a breast cell line bcl-2 was down-regulated by overexpression of a mutant p53 (Halder et al, 1994). In a previous study (Kaklamanis et al, 1996), carcinomas arising from adenomas showed loss of bcl-2 (85% positive adenomas compared with 25% positive carcinomas), implying that during the adenomacarcinoma progression, at the time when p53 mutations usually take place, bcl-2 expression is down-regulated.…”
Section: Discussionmentioning
confidence: 77%
“…Bcl-2 detection in these neoplasms seems to be correlated with favourable clinicopathological parameters and better prognosis (Hague et al, 1994;Ofner et al, 1995;Baretton et al, 1996;Kaklamanis et al, 1996;Watson et al, 1996;Manne et al, 1997;Pereira et al, 1997), although the latter has been controversial (Bosari et al, 1995;Sinicrope et al, 1995;Mosnier et al, 1996). Recently, it was shown that bcl-2 expression did not influence response to chemotherapy for advanced or metastatic disease (Sneider et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that bcl-2 is not only restricted to hematopoietic cells, but also expressed in a variety of epithelial and nonepithelial tissues, led to an increasing on research directed to clarify the role of this molecule in the pathogenesis and prognosis of several malignancies (10) . There is a hypothesis that expression of bcl-2 predisposes to the development of colorectal neoplasms since it may extend survival of cells exposed to carcinogenic agents (21) .…”
Section: Discussionmentioning
confidence: 99%
“…39 Similarly, increased bcl-2 expression has been reported in colorectal adenomas, cervical intraepithelial neoplasia and other precancerous lesions, suggesting that bcl-2 plays an oncogenic role during the early stages of carcinogenesis in cells other than prostate epithelial cells. 17,33,40,41 We are aware of various limitations in the current study. For instance, we did not consider the interaction between variations in the BCL-2 gene and other targets that may regulate or modulate apoptosis, including: (1) oncogenes/tumour suppressor genes such as p53, myc, ras, abl, raf, jun and the bcl-2 family (i.e., other prosurvival and prodeath); (2) hormones (i.e., androgen/androgen receptor), cytokines and growth factor/ growth factor receptors (e.g., tumour necrosis factor-á/ Fas and tumour growth factor-b (TGF-b)/TGF-b receptor), endothelial growth factor/endothelial growth factor receptor and (3) extracellular matrix regulators/cell adhesion molecules.…”
Section: Discussionmentioning
confidence: 97%